Design, Synthesis, and Evaluation of 2‐Anilino‐4‐(3, 5‐dicarboxamidespiperidine)‐pyrimidines as Anaplastic Lymphoma Kinase Inhibitors. (27th August 2015) - Latif, Muhammad; Park, Sangjun; Ali, Imran; Choe, Hyeonjeong; Chae, Chong Hak; Park, Chi Hoon; Kim, Hyoung Rae; Yun, Chang‐Soo; Lee, Kwangho
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10454-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>